Use Of Neurological Rating Scales In The Study Of Pain Symptoms In Salpingoophoritis Complicated With Chronic Pelvic Pain Syndrome. - Ziyayeva E`tiborhon Rasuljonovna; Abdullaev Rasuljon Nabiyevich; Abdullaeva Malika Azimovna (Genius Publishing Group, 2025)
We used neurological rating scales to teach patients to self-report pain symptoms in salpingo-oophoritis complicated by chronic pelvic pain syndrome. The results obtained were recommended for the study of clinical symptoms of salpingo-oophoritis complicated by chronic pelvic pain syndrome.
Keywords: neurological rating scales; pelvic pain syndrome